An unexpected lumbar lesion - Laura Beard; Andrew Downs (Wolters Kluwer Medknow Publications, 2016)
This case report details an interesting case of suspected spinal bifida in an obstetric patient who presented for an elective cesarean section. A large scarred/dimpled area, surrounded by significant hair growth in the region of the lumbar spine had been missed in multiple antenatal and preoperative assessments and was recognized on the day of the surgery as the patient was being prepared for spinal anesthesia. The patient was uncertain regarding the pathology of the lesion, and all investigations relating to this had been undertaken in Pakistan where she lived as a child. General anesthesia was undertaken because magnetic resonance imaging had not been performed and tethering of the spinal cord could not be ruled out clinically. The patient suffered from significant blood loss intra and postoperatively, requiring a two unit blood transfusion. She was discharged after 5 days in the hospital. This case highlights the need for thorough examination in all obstetric patients presenting to the preoperative clinic, focusing on the airway, vascular access, and lumbar spine. Patients may not always disclose certain information due to a lack of understanding, embarrassment, forgetfulness, or language barriers. Significant aspects of their care may have been undertaken abroad and access to these notes is often limited. Preoperative detection of the lesion would have allowed further investigation and imaging of the lesion and enabled more comprehensive discussions with the patient regarding anesthetic options and risk.